A Wearable Molecularly Imprinted Electrochemical Sensor for Cortisol Stable Monitoring in Sweat - Yitao Chen; Zidong He; Yuanzhao Wu; Xinyu Bai; Yuancheng Li; Weiwei Yang; Yiwei Liu; Run-Wei Li (Biosensors)
Cortisol, a steroid hormone, is closely associated with human mental stress. The rapid, real-time, and continuous detection of cortisol using wearable devices offers a promising approach for individual mental health. These devices must exhibit high sensitivity and long-term stability to ensure reliable performance. This study developed a wearable electrochemical sensor based on molecularly imprinted polymer (MIP) technology for real-time and dynamic monitoring of cortisol in sweat. A flexible gold (Au) electrode with interfacial hydrophilic treatment was employed to construct a highly stable electrode. The integration of a silk fibroin/polyvinylidene fluoride (SF/PVDF) composite membrane facilitates directional sweat transport, while liquid metal bonding enhances electrode flexibility and mechanical anti-delamination capability. The sensor exhibits an ultrawide detection range (0.1 pM to 5 μM), high selectivity (over 100-fold against interferents such as glucose and lactic acid), and long-term stability (less than 3.76% signal attenuation over 120 cycles). Additionally, a gradient modulus design was implemented to mitigate mechanical deformation interference under wearable conditions. As a flexible wearable device for cortisol monitoring in human sweat, the sensor’s response closely aligns with the diurnal cortisol rhythm, offering a highly sensitive and interference-resistant wearable solution for mental health monitoring and advancing personalized dynamic assessment of stress-related disorders.